The role of conformity in mask-wearing during COVID-19. - Anna Woodcock; P Wesley Schultz (PLoS ONE)
By September 2020, COVID-19 had claimed the lives of almost 1 million people worldwide, including more than 400,000 in the U.S. and Europe [1] To slow the spread of the virus, health officials advised social distancing, regular handwashing, and wearing a face covering [2]. We hypothesized that public adherence to the health guidance would be influenced by prevailing social norms, and the prevalence of these behaviors among others. We focused on mask-wearing behavior during fall 2020, and coded livestream public webcam footage of 1,200 individuals across seven cities. Results showed that only 50% of participants were correctly wearing a mask in public, and that this percentage varied as a function of the mask-wearing behavior of close and distant others in the immediate physical vicinity. How social normative information might be used to increase mask-wearing behavior is discussed. "Cloth face coverings are one of the most powerful weapons we have to slow and stop the spread of the virus-particularly when used universally within a community setting" CDC Director Dr. Robert Redfield in July 2020.